Profiling competitive Malaysian archers: Musculoskeletal injuries and related risk factors - Ambusam SUBRAMANIAM; Fariza Zainudin FAIRUS; Mon Redee SUT TXI (Baltic Journal of Health and Physical Activity)
Background: Archery requires precision, strength, stamina, and attention, yet musculoskeletal injury data is scarce. The study aimed to profile the musculoskeletal injuries and the associated risk factors among Malaysian archers. Methods: A cross-sectional approach was used to recruit 165 elite archers. The Standardized Nordic Questionnaire (SNQ), adapted risk factors questionnaire, Pittsburgh Sleep Quality Index (PSQI), and Depression Anxiety Stress Questionnaire (DASS-21) were used to screen participants. Results: Shoulder (drawing arm) (54.5%), shoulder (bow arm) (56.4%), upper back (38.8%), lower back (38.2%), and neck (37.6%) musculoskeletal injuries were common. The injuries were reported during training (85.5%), accumulation/overuse injuries (72.1%), and sudden injury onset (44.8%). The results revealed that most of the archers were poor sleepers (53.3%) and suffered from high anxiety (75.5%). Significant associations were seen between the musculoskeletal injuries and the type of coaches (p < 0.05), injury occurrence (training) (p < 0.05), sleep quality (p < 0.05), anxiety (p < 0.05) and stress (p < 0.05). Overall, musculoskeletal injuries and training details showed a weak connection, except for age (rpb = 0.257, p < 0.001). Conclusion: Musculoskeletal injuries, especially in the shoulder and trunk were common. Early screening and risk factor analysis should be focused on injury prevention and management to improve archers' performance.